Consumer acceptability and price sensitivity towards original and imitation products - Lobramonte, Ivy Kenneth Joy R.
The study analyzed the consumer acceptability and price sensitivity in the purchase of imported, imitation and local original products. A total of 143 respondents with varying gender, age and income group, were purposely selected to answer the Price Sensitivity and Consumer Acceptability Questionnaire. The products included in the study were delimited to shoes, shirts, bags, and perfume. Results showed that there are more respondents who purchased imitation products than original. The main reason for purchasing imitation product is the perceived low price. The acceptable prices for imported, imitation, and local original products differ on the products itself as well as the gender and income group of the respondents. Based on Mann Whitney U analysis of two independent samples, males have a higher mean acceptable price for both perfume and rubber shoes than females. Across income groups, Kruskal Wallis One-Way Analysis of Variance showed that there is a difference in acceptable prices for rubber shoes. High-income consumers have the highest mean acceptable price for imported rubber shoes while middle-income consumers have the highest mean acceptable price for imitation rubber shoes. Low-income consumers consistently have the lowest mean acceptable price for imported and imitation rubber shoes. Among those who choose imported, imitation, and local original products, Chi-square analysis showed that there are differences in some products if analyzed across age groups and gender. Women end to purchase original perfumes while men purchase imitation. Across age groups, older consumers prefer original rubber shoes while younger consumer opt for imitation. In relation with consumers' price sensitivity, all respondents, whether buyers of imported imitation and local original products, are more price sensitive when it comes to imitation products and less price sensitive for local original products. It implies that consumers could tolerate high price for an original product while they only have a specific range for the prices of imitation products and if it exceeds the maximum range, a brand switch may occur. Price motivates consumers to purchase imitation products, and thus, it can be a means to prevent the purchase of imitation products. Manufacturers and consumers must take steps on reviewing their price margins from imitation products and see how they can lower the prices that will not sacrifice the good quality of the products and profitability of the manufacturers.